The Alignment of Indonesian Laws with International Legal Instruments on the Rights of Persons with Disabilities - Nurlaily Nurlaily; Ramadani Fitri Sihombing; Rina Shahriyani Shahrullah (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Indonesia promulgated Law No. 8 of 2016 concerning Persons with Disabilities and established the National Action Plan on Human Rights (RANHAM) and Persons with Disabilities (RANPD). At international level, Indonesia ratified the Convention on the Rights of Persons with Disabilities through Law No. 19 of 2011 and it is also committed to achieve Sustainable Development Goals by 2030. The commitment is realized by the National Action Plan for SDGs which also focuses on persons with disabilities. This study aims to analyze the national legal instruments including the national action plans to ascertain their alignments and compliances with the international legal instruments. This study adopts a normative law research by using secondary data which is analyzed based on the content analysis. It finds that all national legal instruments align and comply with the obligations to respect, protect, and fulfill the rights of persons with disabilities mandated by the international legal instruments. Yet, it is unfortunate that the Optional Protocol to the Convention on the Rights of Persons with Disabilities has not been ratified by Indonesia even though it is a significant legal instrument to strengthen the implementation and monitoring of the CPRD.